Effect of Environmental Costs and Environmental Performance on Profitability in Registered Manufacturing Companies on the Indonesian Stock Exchange - Jamali, Hisnol (PT. Riset Press International, 2023)
The purpose of This study is to examine and analyze the effect of (i) environmental costs on profitability, and environmental performance on profitability in manufacturing companies listed on the Indonesia Stock Exchange in the 2019-2020 period. Data collection uses secondary data obtained from the annual report published by the Indonesia Stock Exchange. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange and participating in PROPER in the 2019-2020 period. The sampling technique used was purposive sampling. The data analysis method is in the form of quantitative analysis using multiple linear analysis and hypothesis testing using software E-Views 10. The results showed tha the environmental cost variable has an effect on profitability on Manufacturing companies liested on the Indonesia Stock Exchange in the 2019-2020 period and the Environmental Performance variable has no effect on profitability on Manufacturing companies liested on the Indonesia Stock Exchange in the 2019-2020 period.